Chronic Obstructive Pulmonary Disease and Proteomics: A Match for Success? - Alexandre, Bruno (2012)
Chronic obstructive pulmonary disease (COPD) is characterized by chronic airflow limitation that is not fully reversible even under bronchodilators effect, caused by a mixture of small airway disease and parenchymal destruction. COPD is a major cause of morbidity and mortality in adults, and it is now the fourth leading death cause in the world. Cigarette smoking is the main risk factor for COPD but not all smokers will suffer from COPD, suggesting that genetic and other environmental factors are involved in this pathology. Current diagnosis is based on spirometry, but there is recurrent debate on fixed spirometric thresholds in use that lead to misdiagnosis and/or classification of COPD. The available treatments are not effective to reduce or suppress the progression of COPD. Hence, there is an urgent need to better understand the molecular mechanisms of COPD pathogenesis to provide clinicians with reliable diagnosis and treatment tools for COPD. Proteomics, defined by the comprehensive study of the proteome, has the potential to respond to this need by providing protein profiles of a particular disease and, at the same time, by identifying specific biomarkers that can be used to better understand, diagnose and manage the disease. Here, we shortly review COPD history and pathology and how proteomics can match COPD for success.